2010
DOI: 10.1007/s12272-010-1018-3
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of blood glucose level in physical and emotional stress models: Possible involvement of adrenergic and glucocorticoid systems

Abstract: This study was done to determine the effect of stress on blood glucose regulation in ICR mice. The stress was induced by the electrical foot shock-witness model. Blood glucose level was found to be increased in the electrical foot shock-induced physical stress group. Furthermore, the blood glucose levels were also elevated in the emotional stress group in both physical and emotional stress groups. The blood glucose level reached maximum 30 min after stress stimulation and returned to normal level 2 h after str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Furthermore, we found in the present study that spinal injection of yohimbine alone did not alter the blood glucose level. This finding is different from our recent finding in that systemically administered yohimbine alone decreases the blood glucose level (Sim et al, 2010). Thus, it is suggested that α 2 -drenergic receptors located peripherally appear to be tonically involved in the regulation of the blood glucose level, whereas α 2 -drenergic receptors located in the spinal cord may not.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found in the present study that spinal injection of yohimbine alone did not alter the blood glucose level. This finding is different from our recent finding in that systemically administered yohimbine alone decreases the blood glucose level (Sim et al, 2010). Thus, it is suggested that α 2 -drenergic receptors located peripherally appear to be tonically involved in the regulation of the blood glucose level, whereas α 2 -drenergic receptors located in the spinal cord may not.…”
Section: Discussioncontrasting
confidence: 99%
“…Several lines of evidence suggest that one of the important functions of adrenergic system is the regulation of the blood glucose level. For example, we have recently reported that α-adrenergic receptors are involved in the up-regulation of the blood glucose level induced by stress as well as pain stimulation (Sim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study are, in part, in line with that observed in our previous study, that intraperitoneal (i.p.) injection of yohimbine inhibits physical and emotional stress-induced blood glucose level (Sim et al 2010). Furthermore, (Bialik et al 1998) reported that yohimbine administered i.p.…”
Section: Discussionmentioning
confidence: 99%
“…This significant increment can be attributed to intake of almost 56 g of sugars (glucose 10,5 g and saccharose 43 g) in 500 mL of Red Bull © . However, it has been shown that activation of adrenergic system via physical or emotional stress increases blood glucose levels (max glucose levels reached 30 minutes after stress stimulation) [37]. Furthermore, the effects of caffeine, particularly on glucose metabolism in the sedentary state are detrimental.…”
Section: Discussionmentioning
confidence: 99%